Effect of the Polarization Force on the Dust–Acoustic Soliton Energy. Issue 2 (February 2016) - Mayout, S.; Bentabet, K.; Tribeche, M.
Abstract: The role the polarization force acting on dust particles may play on the energy carried by the dust‐acoustic (DA) soliton is examined. This force is due to the deformation of the Debye sheath around the dust particulates in the background of non‐uniform plasmas. The energy carried by the DA solitons is derived. This energy decreases with an increase in the effects of plasma‐dust particles polarization interaction. This means that when the magnitude of the polarization force approaches the one of the electrical force, i.e, the net force acting on the grains decreases, the DA soliton energy experiences a depletion. As noticed by Khrapak et al. [S.A. Khrapak et al., Phys. Rev. Lett.102, 245004 (2009)], when the polarization force dominates over the electrical one, the plasma can not support DA solitons. This happens whenever the dust grain size exceeds a critical threshold. In this case, the net force acting on the grains is no longer a restoring force. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)